Investigation and development of friction stir welding process for unreinforced polyphenylene sulfide and reinforced polyetheretherketone. (September 2019) - Ahmed, Hossain; van Tooren, MJL; Justice, Jonathan; Harik, Ramy; Kidane, Addis; Reynolds, AP
The joining of thermoplastics through welding offers numerous advantages over mechanical joining. Most importantly, it eliminates the use of costly fasteners and has only a limited effect on the strength of the parts being joined. Since it does not require the introduction of holes, loading pins, and the associated stress concentrations, a specific form of welding, friction stir welding (FSW), was investigated for the creation of butt joints of unreinforced polyphenylene sulfide (PPS) and short carbon fiber (CF)-reinforced polyetheretherketone (PEEK) plates. Unlike metals, analytical models and experimental results show that the heat generated by the FSW tool is insufficient to produce the heat required to weld thermoplastic materials. Therefore, a second heat source is required for preheating these thermoplastics. In this research, a resistance type surface heater was placed at the bottom of two identical weld pieces to produce good quality welds. Two types of shoulder design such as rotating shoulder and stationary shoulder were developed in this study. Taguchi's design of experiment method was utilized to develop the welding process, where heating duration, material temperature, tool rotational speed, and tool traverse speed were used as the welding parameters. One of the process parameters, tool traverse speed, had significant influence on the tensile strength of PPS samples. While PPS sample showed relatively lower tensile strength with higher traverse speed, short CF-reinforced PEEK samples had higher tensile strength with a higher traverse speed. In addition to tensile tests, fracture toughness tests were performed for both PPS and PEEK samples to observe the influence of unwelded segments in the welded parts. In this study, joint efficiency of PEEK samples was found to be higher than that of PPS samples. Micrographs of PEEK samples showed uniform homogenous mixture of part materials.